Answer:
angle E
Step-by-step explanation:
YOYOU CAN CUT BOTH OF THEM AND PLACE IT IN TOP OF EACH OTHER
Answer:
Step-by-step explanation:
-3b - 3b= (-3b)+(-3b)= -6b
Answer:
it is B. -11 and 47
Step-by-step explanation:
you have to take away 47 and 11 and it equals 36.
Answer:
The equation for the axis of symmetry is x=1.5.
Step-by-step explanation:
It is given that a quadratic function passes through the points ( − 5 , − 8 ) and ( 8 , − 8 ) .
In the given points y-coordinates are same, i.e., -8. It means both the points lie on the horizontal line y=-8.
If a quadratic function passes through two points (a,c) and (b,c), then the equation for the axis of symmetry is
![x=\frac{a+b}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7Ba%2Bb%7D%7B2%7D)
According to the given points a=-5, b=8 and c=-8. Put these value in the above formula.
![x=\frac{-5+8}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-5%2B8%7D%7B2%7D)
![x=\frac{3}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B3%7D%7B2%7D)
![x=1.5](https://tex.z-dn.net/?f=x%3D1.5)
Therefore the equation for the axis of symmetry is x=1.5.
Answer:
yes
Step-by-step explanation: